Ion counting in supercapacitor electrodes using NMR spectroscopy. (16th January 2015) - Griffin, John M.; Forse, Alexander C.; Wang, Hao; Trease, Nicole M.; Taberna, Pierre-Louis; Simon, Patrice; Grey, Clare P.
Abstract : 19 F NMR spectroscopy has been used to study the local environments of anions in supercapacitor electrodes and to quantify changes in the populations of adsorbed species during charging. In the absence of an applied potential, anionic species adsorbed within carbon micropores (in-pore) are distinguished from those in large mesopores and spaces between particles (ex-pore) by a characteristic nucleus-independent chemical shift (NICS). Adsorption experiments and two-dimensional exchange experiments confirm that anions are in dynamic equilibrium between the in- and ex-pore environments with an exchange rate in the order of tens of Hz. 19 F in situ NMR spectra recorded at different charge states reveal changes in the intensity and NICS of the in-pore resonances, which are interpreted in term of changes in the population and local environments of the adsorbed anions that arise due to the charge-storage process. A comparison of the results obtained for a range of electrolytes reveals that several factors influence the charging mechanism. For a tetraethylammonium tetrafluoroborate electrolyte, positive polarisation of the electrode is found to proceed by anion adsorption at a low concentration, whereas increased ion exchange plays a more important role for a high concentration electrolyte. In contrast, negative polarization of the electrode proceeds by cation adsorption for both concentrations. For a tetrabutylammonium tetrafluoroborate electrolyte, anion expulsion is observed in the negative charging regime; this is attributed to the reduced mobility and/or access of the larger cations inside the pores, which forces the expulsion of anions in order to build up ionic charge. Significant anion expulsion is also observed in the negative charging regime for alkali metal bis(trifluoromethane)sulfonimide electrolytes, suggesting that more subtle factors also affect the charging mechanism.